Efektivitas Hybrid Method (Metode TMa dan IK) pada Pembelajaran Daring untuk Mata Kuliah Statistik - Ani Mahrita; Fahmi Aulia Rakhman; Meitiana Meitiana (FKIP, Universitas Palangka Raya, 2021)
The purpose of this study was to determine the effectiveness of the hybrid learning method (hybrid method) in economic and business statistics courses. The research method uses a mixed method between a quantitative approach and a qualitative approach using primary data. The data were tested using one of the different test analyzes, namely the Paired-Samples T Test. The findings indicate that an effective hybrid method is used for classes of economic statistics and business. Students prefer to use the IK method combined with the TMa (virtual face) method because they can understand the material quickly and the method is very similar to conventional methods. The theoretical implication of this research is that the hybrid method is better used for online learning methods than the IK method. Meanwhile, the practical implication in this study is that teachers can use the hybrid method for mathematics-based and calculation-based courses because the results of the study show that computation-based statistics courses can be effectively implemented using the hybrid method.